Angular analysis of the B0 → K⁎(892)0μ+μ− decay in proton-proton collisions at s=13TeV - A. Hayrapetyan; A. Tumasyan; W. Adam; J.W. Andrejkovic; L. Benato; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P.S. Hussain; M. Jeitler; N. Krammer; et al. (Physics Letters B)
A full set of optimized observables is measured in an angular analysis of the decay B0→K⁎(892)0μ+μ− using a sample of proton-proton collisions at s=13TeV, collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 140fb−1. The analysis is performed in six bins of the squared invariant mass of the dimuon system, q2, over the range 1.1<q2<16GeV2. The results are among the most precise experimental measurements of the angular observables for this decay and are compared to a variety of predictions based on the standard model. Some of these predictions exhibit tension with the measurements.